Impact of dioxins on reproductive health in female mammals - Aldeli, Nour; Murphy, Denis; Hanano, Abdulsamie (Frontiers in Toxicology, 2024)
Extensive research has been conducted to investigate the toxicological impact of dioxins on mammals, revealing profound effects on the female reproductive system in both humans and animals. Dioxin exposure significantly disrupts the intricate functions of the ovary, a pivotal organ responsible for reproductive and endocrine processes. This disruption manifests as infertility, premature ovarian failure, and disturbances in sex steroid hormone levels. Comprehensive studies, encompassing accidental human exposure and experimental animal data, have raised a wealth of information with consistent yet varied conclusions influenced by experimental factors. This review begins by providing an overarching background on the ovary, emphasizing its fundamental role in reproductive health, particularly in ovarian steroidogenesis and hormone receptor regulation. Subsequently, a detailed examination of the Aryl hydrocarbon Receptor (AhR) and its role in governing ovarian function is presented.The review then outlines the sources and toxicity of dioxins, with a specific focus on AhR involvement in mediating reproductive toxicity in mammals. Within this context, the impact of dioxins, notably 2,3,7,8-tetrachlorodibenzo-p-dioxin (TCDD), on Folliculogenesis and Preimplantation embryos is discussed. Furthermore, the review delves into the disruptions of the female hormonal system caused by TCDD and their ramifications in endometriosis. Notably, variations in the effects of TCDD on the female reproductive and hormonal system are highlighted in relation to TCDD dose, animal species, and age. As a forward-looking perspective, questions arise regarding the potential involvement of molecular mechanisms beyond AhR in mediating the female reproductive toxicity of dioxins.